Autogenous Deformation of Alkali-Activated Blast Furnace Slag Concrete Subjected to Variable Curing Temperatures. (28th April 2019) - Orosz, Katalin; Humad, Abeer; Hedlund, Hans; Cwirzen, Andrzej
Abstract : Deformations of alkali-activated slag concrete (AASC) with high MgO and Al2 O3 content, subjected to variable curing temperature were studied. Sodium silicate and sodium carbonate were used as alkali activators. The obtained results showed development of deformations consisting of both shrinkage and expansion. Shrinkage appeared not to be affected by the activator type, while the expansion developed after the cooling down phase in stabilized isothermal conditions and did not stop within the duration of the tests. X-ray diffraction analysis performed shortly after the cooling down phase indicated the formation of crystalline hydrotalcite, which was associated with the observed expansion. A mixture with a higher amount of sodium silicate showed less expansion, likely due to the accelerated hydration and geopolymerization leading to the increased stiffness of the binder matrix.